Features of organizing strength health programs for women of the second mature age based on a psychophysical approach - Pichugina E.V. ,; Semenov S.A. ,; Reznikov V.A. ,; Antipov A.V. , (Theory and Practice of Physical Culture, 2024)
Objective of the study is to improve the psychophysical state of women of the second mature age based on the assessment of various components of adaptation in the process of strength training in a gym. Methods and structure of the study. The experiment was conducted at the Impulse Sports Palace in Protvino (November 2023 – February 2024). The study involved 27 women aged 35-55 years (average age 47,2), 12 people in the experimental group and 15 in the control group. All participants had various health conditions. To assess heart rate variability, the Psychotest software was used. The assessment of women's physical fitness included: pull-ups from a hanging position while lying on a low bar, push-ups from the knees, lifting the body from a supine position, bending forward from a standing position. Students included in the experimental group were offered a health route that expands adaptation reserves, forming a stable set of defensive reactions that allow them to resist negative influences and maintain health. It is characterized by the use of power loads with a tonic effect, making maximum use of the entire range of stress factors. A distinctive feature was also the presence of cyclicity and staging of loads. Results and conclusions. The inclusion of coordination and psychophysical components in strength training, identification of stress factors and their timely correction made it possible, without increasing the power of strength work, not only to contribute to the improvement of physical conditions comparable to the control group, but also to significantly and reliably increase the indicators of the neuropsychic and regulatory components of adaptation.